Effects of dietary oxidative balance score on diabetic nephropathy and renal function: insights from retrospective and cross-sectional studies - Huang, Yong; Wang, Linfeng; Zhang, Gaojie; Peng, Yueqiang; Xu, Qiao; Wei, Ziling; Yu, Jiang; Zhang, Huayang; Zhang, Yao; Liu, Jiayu (Frontiers in Nutrition, 2025)
BackgroundThe relationship between dietary oxidative balance score (DOBS) and diabetes-related renal events remains unclear.MethodsIn this study, the associations between serum micronutrients and diabetic nephropathy (DN) in participants matched by propensity score (PSM) were retrospectively analyzed. And next, a cross-sectional analysis was performed with the National Health and Nutritional Examination Survey (NHANES) database. Weighted multivariate adjusted logistic regression models, dose–response curves, subgroup analysis, and mediation analysis were the main methods of this study. Finally, sensitivity analyses were performed by PSM and multiple imputation (MI).ResultsRetrospective findings suggest that single antioxidants may not be representative of an individual’s overall antioxidant levels. The results of the cross-sectional study indicated that the higher the DOBS, the greater the beneficial effects on DN [Q4 vs. Q1: OR (95% CI): 0.78 (0.63, 0.96), p for trend = 0.008] and renal function in DN [Q4 vs. Q1: β (95% CI): 5.395 (1.590, 9.199), p for trend = 0.004]. The above correlations were linear negative correlation (p for nonlinear = 0.989) and linear positive correlation (p for nonlinear = 0.593) respectively. Chronic inflammation mediated the above associations to some extent. The results of sensitivity analysis were consistent with the original analysis.ConclusionHigher dietary antioxidant exposure has a positive effect on DN and renal function in DN, mediated partially by chronic inflammation.